Efektivitas Senam Aerobik terhadap Penurunan Berat Badan pada Penderita Obesitas di Sanggar Senam Medan - Sulaiman, Sulaiman; Maryaningsih, Maryaningsih; Agustina, Dewi; Anggriani, Anggriani (Jurnal Riset Hesti Medan, 2023)
Over vegetables and fruits and lack of daily activities resulting from obesity. The factor of obesity is due to the high intake that enters the body compared to the intake of energy released because of the lack of activity and low metabolism of the body. Exercise is the best option compared to diet in losing weight, one of the exercises that can be done is aerobic gymnastics. Method: used in this study is a quasi-experiment with the design of one group pre test and post test with purposive sampling technique with a total sample of 16 people. The data were analyzed with the wilcoxon test. Results: from the wilcoxon test obtained 0.000 where less than 0.005 (sig 0.000<0.005) so that the hypothesis decision that there is an effect of aearobic gymnastics exercises on weight loss in obese people in the Gymnastics Studio Karina Ina Medan. Conclusion: what was obtained from the study was that there was an influence of aearobic gymnastics exercises on weight loss in obese people in the Karina Ina Medan gymnastics studio